Turkey : a regional power in the making - Aksu, Kenan, 1978- (Cambridge Scholars Publishing, 2013)
Turkey, a bridge between the East and the West, has emerged as a true regional power and a significant global player since the end of the Cold War. Especially after the 2000s, Turkey has become a success story in every aspect of the social, political, and economic spectrums. As a result of the pace of the developments, academic studies fall behind Turkey in analysing and evaluating the changes it has encountered. Literature focusing on Turkey continuously needs rapid updating to fulfill the a ...